Plant density in production of mini lettuce cultivars in organic system management - Takahashi, Keiko [UNESP]; Cardoso, Antonio Ismael Inacio [UNESP] (Assoc Brasileira Horticultura, 2014)
Production of mini vegetables in organic system is a good alternative to improve profit, but there are no researches about the optimum plant density for these cultivars in Brazilian conditions. Two experiments were conducted to evaluate the production of mini lettuce cultivars in different plant densities. Experiment 1 was conducted from January 1th (sowing) to February 10th (harvesting), 2012. The experimental design was completely randomized blocks, with six treatments in factorial scheme, 3 mini lettuce cultivars (Tudela, Renoir and Sartre) x 2 spacing between plants (16 and 20 cm), with eight replications and plots (2.04 m(2)) with six rows, spaced 15 cm. Experiment 2 was conducted from June 6th (sowing) to July 18th (harvesting), 2012. The cultivars Sartre and Renoir were evaluated under four plant densities (444,444; 333,333; 266,667 and 200,000 plants ha(-1), corresponding to spacing of 15x15, 15x20, 25x15 and 25x20 cm, respectively). Eight treatments were defined by a factorial scheme 2 (cultivars) x 4 (plant densities) and arranged in a completely randomized block design, with nine replications and plots with 2.04 m2. The evaluated characteristics in both experiments were total and marketable fresh weight per plant, plant dry weight, plant diameter and height, marketable yield and discard percentage. In first experiment, during the summer, cultivar Sartre showed the highest marketable fresh weight (72 g plant(-1)). Heaviest plants (91.6 g plant(-1)) were obtained with the higher plant spacing, but the highest yield (2.51 kg m(-2)) was obtained with the smaller spacing. In winter, plants with higher total (190 g plant(-1)) and marketable (146 g planta(-1)) fresh weight were obtained with cultivar Sartre, and the same was observed in low plant density. However, the higher plant density, the higher the yield.

A produção de mini hortaliças em sistema orgânico é uma boa alternativa para aumentar os lucros do produtor; no entanto, não há pesquisas sobre a melhor densidade de plantio para estas cultivares nas condições brasileiras. Dois experimentos foram conduzidos para avaliar a produção de cultivares de mini alface em diferentes densidades de plantio. O experimento 1 foi conduzido de 1 de janeiro (semeadura) a 10 de fevereiro (colheita) de 2012. O delineamento experimental utilizado foi blocos ao acaso, com seis tratamentos em esquema fatorial, 3 cultivares de mini alface (Tudela, Renoir e Sartre) x 2 espaçamentos entre plantas (16 e 20 cm), com oito repetições e parcelas (2,04 m2 ) com seis linhas espaçadas em 15 cm. O experimento 2 foi conduzido de 6 de junho (semeadura) a 18 de julho (colheita) de 2012. As cultivares Sartre e Renoir foram avaliadas em quatro densidades de plantio (444.444, 333.333, 266.667 e 200.000 plantas ha-1, correspondendo aos espaçamentos, 15x15, 15x20, 25x15 e 25x20 cm, respectivamente). Os oito tratamentos foram definidos pelo esquema fatorial 2 (cultivares) x 4 (densidades de plantas) e dispostos em blocos ao acaso, com nove repetições e parcelas com 2,04 m2 . As características avaliadas em ambos experimentos foram massas de matéria fresca total e comercial, massa de matéria seca, diâmetro e altura das plantas, produtividade comercial e porcentagem de descarte. No primeiro experimento, durante o verão, a cultivar Sartre apresentou maior massa da matéria fresca comercial (72 g planta-1). Foram obtidas plantas mais pesadas (91,6 g planta-1) no maior espaçamento, porém, a maior produtividade (2,51 kg m-2) foi obtida com o menor espaçamento. No inverno, foram obtidas plantas com maiores massa fresca total (190 g planta-1) e comercial (146 g planta-1) na cultivar Sartre, assim como nas menores densidades de plantio. Porém, quanto maior a densidade, maior a produtividade.
Densidade de plantas na produção de cultivares de mini alfaces em sistema orgânico
Keywords: Lactuca sativa; Spacing; Yield; Lactuca sativa; Espaçamento; Produtividade